Pengaruh Produk, Harga, Tempat, Promosi Terhadap Keputusan Pembelian Hijab Pada Konsumen Varisya Collection - Novarisya Putri Ramadhani; Afi Rachmat Slamet; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The goal of this research is to determine how elements such as product, price, location, and promotion affect consumers' decisions to buy. Using a quantitative approach, the research was conducted. The Consumers of the Products are the population in this study Varisya Collection Tumpang. Although this study's sample was calculated using the Slovin formula so there are 112 samples. Using a questionnaire, we collected primary data. The data analysis technique used includes the instrument test for validity and reliability, the traditional assumption test for Hypothesis testing for partial test, stealth test, and coefficient of determination, as well as normality, multicollinearity, and heteroscedasticity. According to the research's partial findings, product has a major impact on buying decisions, price has a negative impact on buying decisions but still has a considerable impact, location has no significant impact on buying decisions, and promotion has a significant impact on buying decisions. Keyword : Product, Price, Place, Promotion on Purchasing Decisions